An Analysis of Students’ Reading Interest during Learning From Home amidst the Covid-19 Pandemic - Sri Utami; Jumaidi Nur (IJEE (Indonesian Journal of English Education), 2021)
ABSTRACTThis study aimed to analyze students’ reading interest during the learning-from-home policy in the Covid-19 pandemic time, and it was conducted at the English Department of the University of Kutai Kartanegara in Tenggarong. This descriptive study employed a qualitative approach with a survey design that involved 79 students from the second, fourth, and sixth semesters as participants. The data were obtained through a questionnaire and interview, and they were then analyzed descriptively. Results of this study showed that during the learning-from-home policy students liked to read anything but lecture materials. They argued that reading was tedious and difficult. They preferred reading fiction to reading non-fiction and preferred reading online to reading offline. They read 15-30 minutes a day and only read 1-3 books within five months of learning from home. Their reading materials came from online and offline sources, from websites, and print books by using smartphones. The type of material that was mostly read was novels especially romantic ones. This study suggests that teachers should present lecture materials in such a way that students would be interested in reading them for certain reasons academically or personally.ABSTRAKPenelitian ini bertujuan untuk menganalisis minat baca siswa selama belajar dari rumah pada waktu pandemi Covid-19, dan dilakukan di Jurusan Bahasa Inggris Universitas Kutai Kartanegara di Tenggarong. Penelitian ini menggunakan pendekatan kualitatif dengan menggunakan studi deskriptif jenis survei yang melibatkan 79 mahasiswa semester dua, empat, dan enam sebagai partisipan. Data diperoleh melalui angket dan wawancara, kemudian dianalisis secara deskriptif dan disajikan dalam bentuk tabulasi frekuensi dan persentase, serta dalam bentuk naratif. Hasil penelitian menunjukkan bahwa siswa suka membaca apa saja kecuali materi perkuliahan selama belajar dari rumah. Mereka berpendapat bahwa membaca itu membosankan dan sulit. Mereka lebih suka membaca fiksi daripada membaca non-fiksi dan lebih suka membaca online daripada membaca offline. Mereka membaca 15-30 menit sehari dan hanya membaca 1-3 buku dalam waktu lima bulan belajar dari rumah. Sumber bacaan mereka berasal dari online dan offline, dari Website dan buku cetak dengan menggunakan smartphone. Jenis materi yang paling banyak dibaca adalah novel terutama novel romance. Studi ini menunjukkan bahwa terdapat berbagai alasan mengapa fenomena tersebut terjadi.